2006
DOI: 10.1534/genetics.105.051375
|View full text |Cite
|
Sign up to set email alerts
|

A Deletion at the MouseXistGene ExposesTrans-effects That Alter the Heterochromatin of the Inactive X Chromosome and the Replication Time and DNA Stability of Both X Chromosomes

Abstract: The inactive X chromosome of female mammals displays several properties of heterochromatin including late replication, histone H4 hypoacetylation, histone H3 hypomethylation at lysine-4, and methylated CpG islands. We show that cre-Lox-mediated excision of 21 kb from both Xist alleles in female mouse fibroblasts led to the appearance of two histone modifications throughout the inactive X chromosome usually associated with euchromatin: histone H4 acetylation and histone H3 lysine-4 methylation. Despite these eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 96 publications
(136 reference statements)
3
39
0
Order By: Relevance
“…A link between BRCA1 and XIST has been investigated intensively (35)(36)(37)(38)(39). Furthermore, the deletion of Xist in mice leads to hematologic malignancies (40) and genomic instability of the X chromosome (41). One hypothesis would be that true BRCA1-loss-driven cancers require (a sequence of) events or multiple functions of BRCA1 that results in losing the inactive X chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…A link between BRCA1 and XIST has been investigated intensively (35)(36)(37)(38)(39). Furthermore, the deletion of Xist in mice leads to hematologic malignancies (40) and genomic instability of the X chromosome (41). One hypothesis would be that true BRCA1-loss-driven cancers require (a sequence of) events or multiple functions of BRCA1 that results in losing the inactive X chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, nonmeiotic pairing can influence gene regulation and DNA repair through the processes of transvection (reviewed by Pirrotta 1999;Wu and Morris 1999;Duncan 2002;Kassis 2002;Kennison and Southworth 2002) and recombination (reviewed by Gloor 2002;Wyman et al 2004; also see Rong and Golic 2003), respectively. Pairing of homologous chromosomal regions has also been implicated in mammalian X-inactivation (Marahrens 1999;Bacher et al 2006;Diaz-Perez et al 2006;Xu et al 2006) and imprinting (Lasalle and Lalande 1996;Riesselmann and Haaf 1999). Intriguingly, a reduced level of pairing at imprinted regions may be associated with syndromes such as autism and the Prader-Willi and Angelman syndromes (Lasalle and Lalande 1996;Thatcher et al 2005).…”
mentioning
confidence: 99%
“…The precise mechanism by which XIST recruits PRC1/2 to the X-chromosome is still unclear, as X-inactivation requires an evenly distributed presence of PRC1/2 across the Xi so as to ensure the proper silencing of both coding and noncoding transcripts [ Figure 2B]. Some have indicated that the silencing of Xi is accompanied by phosphorylation events on p53, indicating XIST cooperates with the p53 DNA-repair machinery during X-inactivation [78] . Given other ncRNAs such as miR-34 are known regulators of TP53 expression in cancer cell lines as well as during development [79] , this raises the notion that lincRNAs cooperate with ncRNAs to carry out specific cellular programs.…”
Section: Lncrna Nomenclaturementioning
confidence: 99%